Numerical Simulation of a Steel Weld Joint and Fracture Mechanics Study of a Compact Tension Specimen for Zones of Weld Joint - BENSARI AHMED; Ould Chikh El Bahri; Bouchouicha Benattou; Tirenifi Malika (Fracture and Structural Integrity)
To evaluate the integrity of a structure consists to prove his ability to perform his mechanical functions for all modes of loading, normal or accidental, and throughout its lifespan. In the context of nuclear safety, for the most important welded structures such as the tank or the primary circuit, we consider that the presence of a degradation grouping several aspects, such as cracks which created during welding. We seek then, from the sizing, to show the mechanical strength for this degraded mode. We also seek; to show the mechanical strength of a structure in the presence of a crack when defects have been detected during an inspection, in this context, the fracture mechanics provides the necessary tools to analyze cracked components. Its purpose is to establish a fracture criterion to foreordain the loading margins in normal or accidental operating conditions. Each type of rupture must be the subject of a specific characterization.